2010
DOI: 10.1021/jp102349m
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Electron Transfer from Ruthenium-Polypyridyl Compounds to Anatase TiO2 Nanocrystallites: Evidence for a Stark Effect

Abstract: Photophysical studies were performed with [Ru(dtb)(2)(dcb)](PF(6))(2) and cis-Ru(dcb)(dnb)(NCS)(2,) where dtb is 4,4'-(C(CH(3))(3))(2)-2,2'-bipyridine, dcb is 4,4'-(COOH)(2)-2,2'-bipyridine, and dnb is 4,4'-(CH(3)(CH(2))(8))(2)-2,2'-bipyridine), anchored to anatase TiO(2) particles (∼15 nm in diameter) interconnected in a mesoporous, thin film (∼10 μm thick) immersed in Li(+)-containing acetonitrile electrolytes. Pulsed-laser excitation resulted in rapid, nonquantitative excited-state injection into TiO(2) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
98
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(113 citation statements)
references
References 84 publications
14
98
1
Order By: Relevance
“…We find evidence for the transient build-up of a local Stark effect, [28][29][30] where the electric field exerted by the D149 + radical cations and injected electrons influences the ground-state absorption spectrum of D149. In addition, undulatory structure in the transient spectra can be traced back to injected electrons modifying the optical response of the thin film.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…We find evidence for the transient build-up of a local Stark effect, [28][29][30] where the electric field exerted by the D149 + radical cations and injected electrons influences the ground-state absorption spectrum of D149. In addition, undulatory structure in the transient spectra can be traced back to injected electrons modifying the optical response of the thin film.…”
mentioning
confidence: 84%
“…This leads us to the conclusion that these spectral dynamics are likely dominated by the ''local Stark effect'' proposed by Cappel et al 28 and Meyer and co-workers. 29,30 Further support comes from the study of Cappel et al 28 They showed that PIA spectra of D149 on TiO 2 were dominated by the firstorder Stark effect: for the limiting case of aligned D149 molecules and an electric field acting normal to the surface, the change in absorbance (DOD) should be proportional to the first derivative of the steady-state absorption spectrum of D149. 28 The scaled derivative of the inverted steady-state absorption spectrum is depicted in Fig.…”
mentioning
confidence: 98%
“…The widespread investigation of Ru II -polypyridyl complexes over the past 30 years largely has roots in their impressive photophysical and redox properties, which make them amenable for adaptation to a myriad of technologies including dye-sensitized solar cells (DSSCs), [1][2][3][4][5][6][7] solar fuels photochemistry, [8] light-emitting electrochemical cells, [9] photoluminescence sensors, [10] biophotonics, [11,12] photochromics, [13][14][15][16][17][18] water-oxidation catalysis, [19] low-power photon upconversion, [20][21][22][23] as well as fundamental studies in photoinduced electron and energy transfer. [24][25][26][27][28][29] Interestingly, the related class of Ru II molecules that incorporate one or more cyclometalating ligands into their structure were only sparingly investigated over the same time frame.…”
Section: Introductionmentioning
confidence: 99%
“…The ruthenium dyes produce overall photo-electrical conversion efficiency of higher than 10% due to their broad photoresponse area [3][4][5]. However, the manufacturing costs and environmental issues of the ruthenium sensitizers limit their large-scale application.…”
Section: Introductionmentioning
confidence: 99%